The Effect of Inorganic Acid Activation on the Metal Oxide Content of Natural Montmorillonite from Gowa Regency - Suriati Eka Putri; Sumiati Side; Nita Magfirah Ilyas; Diana Eka Pratiwi; Abd Rahman (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Natural montmorillonite has attracted considerable attention due to its high cation exchange capacity, layered structure, and potential applications as adsorbents and catalyst supports. However, it generally contains impurity oxides that affect its physicochemical properties. This study aimed to investigate the effect of inorganic acid activation on the metal oxide content and crystalline characteristics of natural montmorillonite obtained from Gowa Regency, South Sulawesi, Indonesia. The montmorillonite samples were activated using 2 M HCl and 2 M H₂SO₄ through acid leaching treatment. The metal oxide composition and crystalline phases were characterized using X-ray fluorescence (XRF) and X-ray diffraction (XRD), respectively. The XRF results revealed that Fe₂O₃ was the dominant impurity oxide in natural montmorillonite with a concentration of 31.61%. After acid activation, the Fe₂O₃ content decreased significantly to 21.78% for HCl-treated MMT and 18.83% for H₂SO₄-treated MMT, indicating effective removal of iron oxide impurities. In contrast, the SiO₂ content increased from 39.51% to 40.13% and 41.02% after HCl and H₂SO₄ activation, respectively. XRD analysis confirmed the presence of quartz silica, alumina, and hematite phases, with diffraction peaks at 2θ ≈ 26.6°, 34.2°, and 50.1°, respectively. Acid activation also reduced the average crystallite size from 41.2 nm in natural MMT to 35.1 nm and 29.9 nm after HCl and H₂SO₄ treatment, respectively. The results demonstrate that inorganic acid activation effectively modified the oxide composition and crystalline structure of natural montmorillonite, particularly through the removal of hematite impurities and enhancement of silica-rich phases. Therefore, acid-activated montmorillonite shows promising potential for adsorption and catalytic applications.